Case Report: a family report of hereditary pancreatitis caused by SPINK1 and PRSS1 gene mutations - Xu, Jing; Hu, Ying; Xiao, Banghui; He, Juan; Zhang, Miao; Wang, Rui; Peng, Nianchun (Frontiers in Genetics, 2025)
Hereditary pancreatitis (HP) is a rare genetic disorder of the pancreas. We report a case of a 20-year-old woman presenting with classic features of lean diabetes mellitus, chronic diarrhea, and diabetic ketoacidosis but notably without abdominal pain. Imaging revealed pancreatic calcification. Genetic testing identified pathogenic compound mutations in SPINK1 (c.194+2T>C) and PRSS1 (c.623G>C), confirming a diagnosis of HP. Family screening showed her mother carried a homozygous SPINK1 mutation, while her siblings variably carried heterozygous SPINK1 and/or PRSS1 mutations. All family members with both variants, except the third sister, had pancreatic calcifications. Diabetes was observed in the proband, her mother, and her first and second sisters. This case highlights that in patients under 25 years of age presenting with lean body habitus, diarrhea or steatorrhea, poor islet function, and a family history of diabetes—despite lacking overt abdominal pain—HP should be considered as a differential diagnosis.